Qualitative Assessment for Milk Adulteration: Extent, Common Adulterants, and Utility of Rapid Tests - Lakshya Garg; Shakila Mulla (Wolters Kluwer Medknow Publications, 2024)
Background: The adulteration of milk is an important issue that needs to be addressed because of its deleterious effects on health. Detection of adulterants in milk can be done in laboratories or by purchasing adulteration detection kits. There are few home-based rapid tests to detect common milk adulterants, which are less known by our community. Objectives of this study were to estimate the proportion of milk adulteration and to identify common adulterants, to determine the association of milk adulteration with gastrointestinal and renal diseases; and also to validate rapid home-based tests by comparing its result with standard milk adulteration detection kit. Materials and Methods: A community-based study was conducted on 330 medical and paramedical staff. Collected milk samples during family visits were tested by standard milk adulteration detection tests and rapid home-based tests. Results: Among 330 tested milk samples, 233 samples were adulterated with one or more than one adulterant. The most common adulteration observed was the addition of water to milk, followed by detergent, urea, and neutralizer. The specificity of the rapid tests was found to be almost 100% in the detection of water and detergent in milk and accuracy was above 80%; with "substantial agreement" (kappa = 0.7) between rapid tests and standard tests on kappa statistics. Conclusion: The present study has identified a large extent of milk adulteration and common adulterants, which may have harmful effects on health. The utility of home-based rapid tests is clearly proven to detect common adulterants.